2018
DOI: 10.1007/s00404-018-4713-9
|View full text |Cite
|
Sign up to set email alerts
|

Single versus double-balloon catheters for the induction of labor of singleton pregnancies: a meta-analysis of randomized and quasi-randomized controlled trials

Abstract: Measured primary outcome measures were similar regardless of the type of device used for labor induction of singleton pregnancies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 29 publications
1
16
1
Order By: Relevance
“…It should be noted that findings from a recent meta-analysis of six trials suggest there are no differences in labor induction outcomes (i.e., time to delivery, vaginal and cesarean delivery rates, maternal satisfaction) with single versus double balloon catheters. 86…”
Section: Limitations Of Trials On Labor Inductionmentioning
confidence: 99%
“…It should be noted that findings from a recent meta-analysis of six trials suggest there are no differences in labor induction outcomes (i.e., time to delivery, vaginal and cesarean delivery rates, maternal satisfaction) with single versus double balloon catheters. 86…”
Section: Limitations Of Trials On Labor Inductionmentioning
confidence: 99%
“…Currently, most studies have found that the single and the double balloon catheters have similar e ciency, safety and patient satisfaction, but the single-balloon method is considered to be more cost-effective and is more easily accepted by patients (12,19,15,20). Other authors (21) found that the mean intervention to the birth time, the vaginal delivery and the cesarean section rates, and maternal satisfaction were similar for both kind of balloons. Fang Yang (22) concluded that there was no signi cant difference in the estimated values for the cesarean section and vaginal delivery rate in 24 hours, nor in the average delivery time and improvement of Bishop score between the two groups.…”
Section: Discussionmentioning
confidence: 99%
“…However, some scholars have con rmed that there are differences in the e cacy of the double balloon and the single balloon induced labor. Other authors (21) showed that there was a signi cant difference in the change of the Bishop score in the single balloon group compared with the double group, suggesting that the single balloon has a more signi cantly signi cant increase in the cervical Bishop score while Hoppe et al (24) reported that among the cohort of primipara women, a greater proportion of the double balloon group achieved a Bishop score ≥6 at the time of catheter removal and vaginally delivered labor compared to the single-balloon catheter assisted labor. No difference in the catheter type for achieving a Bishop score ≥6 or vaginal delivery among multiparous women was detected, suggesting that the 80 mL double-balloon catheter is more effective than the 30 mL single-balloon catheter for pre-induction of cervical ripening and achieving a vaginal delivery in primipara.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cervicovaginal application of a DBC, such as the Cook or Atad balloons, applies pressure within the lower uterine segment in addition to bidirectional pressure on the cervix, increasing local prostaglandin production. Studies comparing single cervical balloons with DBC show no differences in mode of delivery, patient satisfaction or complication rates 77 78. We have selected FCB as the trial intervention rather than DBC as it is significantly cheaper and more readily obtained; furthermore, mechanical induction is uncommon in our institution and this represents an opportunity to improve local VBAC management.…”
Section: Discussion Ethics and Disseminationmentioning
confidence: 99%